Soft annealing effect on the properties of sputter grown Cu2ZnSnS4 (CZTS) thin films for solar cell applications. (2021) - Pandharkar, Subhash; Punde, Ashvini; Nasane, Mamta; Doiphode, Vidya; Shinde, Pratibha; Vairale, Priti; Hase, Yogesh; Bhorde, Ajinkya; Waghmare, Ashish; Rondiya, Sachin; Prasad, Mohit; Jadkar, Sandesh
Abstract: In present study, CZTS films were fabricated using 2 different processes and their properties have been compared. The first is a 2-stage process which includes deposition of CZT followed by sulfurization and the second is a 3-stage process which includes deposition of identical CZT, soft annealing (pre-heating) and sulfurization. Structural, morphological, optical and compositional properties of CZTS films are investigated by XRD, Raman spectroscopy, FE-SEM, UV–Visible spectroscopy, EDS and photoresponse measurements. Structural analysis revealed that films prepared by both processes have polycrystalline kesterite-CZTS structure and exhibit prefered orientation along (1 1 2) direction. It has been observed that soft annealing temperature in 3-stage process significantly improve the crystal quality of CZTS films. Surface morphology of films sulfurized at 550 °C shows a uniform and compact micrograin (∼0.31 µm) without cracks. The soft annealing temperature significantly improves micrograin size (∼0.49 µm) and compactness of CZTS films. UV–Visible spectroscopy showed that the band gap of all CZTS films is in optimal range. The CZTS films fabricated by 3-stage process, exhibits high photocurrent response under intermittent visible-light irradiation, implying that they can useful as an absorber layer in solar cells.